(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
There are many conventional methods for predicting the first lactation milk yield in 305 days (FLMY) based on fortnightly part milk yield data in dairy cattle. The different methods used are based on data available over different years as implicated under farm and field conditions. These fortnightly test day milk yields could be utilized in the estimation of 305-day milk yield by ratio method and multiple regression methods. The Sahiwal cattle can be selected for higher FLMY utilizing fifth fortnightly day milk yield (FTDY-5), FTDY-6, FTDY-7, FTDY-8, FTDY-11, and FTDY-18 test day yields. Selection can be carried out for higher first lactation milk yield based on fortnightly test day milk yields in the case of Sahiwal and its crossbred cattle.